ITGAX promotes gastric cancer progression via epithelial-mesenchymal transition pathway - Hu, Jiali; Cao, Jing; Huang, Shanshan; Chen, Yang (Frontiers in Pharmacology, 2025)
Gastric cancer is the fifth most common cancer and the fourth leading cause of cancer-related deaths worldwide, accounting for nearly 800,000 fatalities annually. ITGAX (Integrin alpha X) is closely associated with immune cells, such as macrophages and dendritic cells. Its involvement in gastric cancer was identified through an analysis of The Gene Expression Omnibus (GEO) database, which highlighted ITGAX as one of four key gastric cancer-related genes. Our study demonstrates that ITGAX expression is significantly elevated in tumor tissues compared to normal tissues and is positively correlated with clinical prognosis in gastric cancer patients from the GEO database. Moreover, ITGAX enhanced cell proliferation, invasion, and tumorigenic capacity in mouse models. Furthermore, we explored the underlying role of ITGAX using Kyoto Encyclopedia of Genes and Genomes (KEGG) and protein-protein interaction networks (PPI) analysis. Our findings reveal that ITGAX promotes gastric cancer progression by driving epithelial-mesenchymal transition pathway (EMT), suggesting its potential as a biomarker for early diagnosis and prognosis in gastric cancer.